Analisis Struktur dan Kebahasaan pada Media Surat Kabar Daring Kompas.com sebagai Sumber Belajar Teks Berita - Risda Ayu Prihantiwi; Deby Luriawati Naryatmojo (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Students are the next generation of the nation and need to be equipped with information or news that is up-to-date and contains positive and motivating values. This can be influenced by the use of good and correct language in providing information that can be accounted for its truth. The lack of critical reading literacy can affect the application of values ​​and mindsets of each individual. The development of increasingly sophisticated technology also has positive and negative impacts, especially in the use of inappropriate language that has an impact on misunderstandings related to the intent and purpose of information. In addition, the news presented does not match the elements of the news text, causing chaos, misunderstanding, and the emergence of hoax news that is easily spread to the public. This study aims to help students analyze the structure and language that is good and correct in the news text used as a learning resource. This study is also expected to provide both theoretical and practical benefits. Theoretically, the results of this study can be one of the literature on news texts that contain linguistic analysis found in online newspaper media. In addition, this study does not only discuss language, but also provides information or understanding regarding the characteristics of each online newspaper media that can be considered as a learning resource in schools. Practically, the results of this study are expected to be useful for teachers to understand and meet students' needs according to the competencies to be achieved in the learning process. In addition, the results of this study are expected to prevent language errors, especially in news texts so that the information conveyed can be well received by the public, especially students.